PENGARUH STRES KERJA, KOMPENSASI , SERTA LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN INSTALASI PENGOLAHAN AIR LIMBAH SEWON - Saleh, Sandyka Yanuar; Kirana, Kusuma Chandra; Herawati, Jajuk (2021)
The success of Sewon Wastewater Treatment cannot be separated from the performance of its employees. Productive human resource performance is created if the work environment is conducive, gets appropriate compensation and the company can anticipate work stress. Work stress, compensation, work environment greatly affect the success of employee performance at the Sewon Wastewater Treatment Plant. The sample method is non-probability with a saturated sample. The number of questionnaires processed was 49 of the 82 questionnaires distributed. The findings show that work stress is negative for employee performance, then compensation and work environment have a positive and significant impact on employee performance. Keywords: work stress, compensation, work environment, and employee performance